Better with each throw - a study on calibration and warm-up decrement of real-time consecutive basketball free throws in elite NBA athletes - Phatak, A.; Mujumdar, U.; Rein, R.; Wunderlich, F.; Garnica, M.; Memmert, D. (German Journal of Exercise and Sport Research, 2020)
Calibration and warm-up decrement seem to influence performance in sensorimotor skills that are repeatedly performed in succession. Current evidence suggests that error rates are greatest for the first of multiple attempts when performing the same sensorimotor task repeatedly. The aim of the present study is, therefore, to study the calibration effect in sets multiple free throws for National Basketball Association (NBA) players by analyzing single, double and triple sets of free throws and their success rates for each of the respective attempts. We hypothesized that the success rate of subsequent free throws is greater compared to immediately preceding throws. To this end, data from the NBA seasons between 2006 and 2016 totaling 610,049 shots and 1098 players were obtained. For a set of double free throws, the success rate of the second throw was greater compared to the first throw. For triple free throws the success rate increased with each successive throw. The results demonstrate differences between consecutive throwing percentages. In conclusion, the current study supports previous findings in darts that calibration effects may explain the underlying increases in performance during repetitive execution of complex sensorimotor skills. Therefore, the present study extends the previous findings to full body movements involving many biomechanical degrees of freedom.